Impact of COVID-19 on China Railway Express: A More State-led Approach to Develop Freight Train - Jiaqi YANG (Utan Kayu Publishing, 2024)
The China Railway Express (CR Express) is an international railway freight train organised by China Railway Corporation, which has been travelling between China and Europe since 2011. Since its inception, the volume of the CR Express train has increased year by year and the variety of foreign trade goods has been enriched. During the COVID-19, traditional transport channels such as sea and air transport were severely hit, while the volume and product range of the CR Express grew against the trend. Under the impact of the epidemic, the booming development of the CR Express trains could not have been achieved without the guidance and support of the state, i.e. the CR Express trains moved towards a more state-led development model.